1997
DOI: 10.1006/viro.1997.8689
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Specific Repression of Cotranslational Translocation of the Hepatitis B Virus Envelope Proteins Coincides with Binding of Heat Shock Protein Hsc70

Abstract: The large L envelope protein of the hepatitis B virus has the peculiar capacity to adopt two transmembrane topologies. The N-terminal preS domain of L initially remains in the cytosol while the S domain is cotranslationally inserted into the endoplasmic reticulum membrane. The preS region of about half of the L molecules' is posttranslationally translocated to the lumenal space. We now demonstrate that the repression of cotranslational translocation of preS is conferred by a preS1-specific sequence. By analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 29 publications
5
59
0
1
Order By: Relevance
“…We demonstrate that L interacts with cytosolic Hsc70 and ER-resident BiP in vivo. Consistent with our previous in vitro results (22), the preS1 domain of L was deemed to be the likely target for Hsc70 and also for BiP because both chaperones failed to recognize the HBV M and S proteins that share the primary sequence of L except for preS1. The lack of chaperone binding of M and S coincides with their classical cotranslational folding pathway and hence provides evidence for functional roles of Hsc70 and BiP in controlling the nonclassical translocation of L. In support, we observed that artificial enforcement of cotranslational preS translocation of L blocked its association with Hsc70, implicating this chaperone to be responsible for the suppression of the cotranslational preS import into the ER.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…We demonstrate that L interacts with cytosolic Hsc70 and ER-resident BiP in vivo. Consistent with our previous in vitro results (22), the preS1 domain of L was deemed to be the likely target for Hsc70 and also for BiP because both chaperones failed to recognize the HBV M and S proteins that share the primary sequence of L except for preS1. The lack of chaperone binding of M and S coincides with their classical cotranslational folding pathway and hence provides evidence for functional roles of Hsc70 and BiP in controlling the nonclassical translocation of L. In support, we observed that artificial enforcement of cotranslational preS translocation of L blocked its association with Hsc70, implicating this chaperone to be responsible for the suppression of the cotranslational preS import into the ER.…”
Section: Discussionsupporting
confidence: 88%
“…2 A, lane 1). N-linked glycosylation of the slower migrating forms had been confirmed previously by treatment with PNGase F (22). Importantly, both forms of L were efficiently coimmunoprecipitated with Hsc70 ( Fig.…”
Section: Interacts With Hsc70 and Bip In Vivosupporting
confidence: 76%
See 3 more Smart Citations